A Comparative Study of the Coagulation Systems and Inflammatory Profiles of Patients with Myalgic Encephalomyelitis/Chronic Fatigue Syndrome and Patients with Long COVID - Arron, Hayley Emma (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2025.